Investigating business process management on environmental performance considering the mediating role of information technology - Lida Liu; Lan Chen (Heliyon)
Businesses in the current world need to plan in light of rapidly evolving factors including technology, equipment, the competitive market, customers, etc. To address the ever-increasing environmental concerns, corporations have implemented new policies and procedures. In this research, we apply a technological intervention to analyze how the uncertain nature of business management affects environmental performance at Huangshi in Hubei. The study's focus, quantitative nature, and descriptive-analytical approach all make it a subset of applied research. The library study approach is used to gather data for the purpose of compiling theoretical underpinnings and research material. Statistical packages like SPSS and PLS are used to do both descriptive and inferential analyses on the data. The hypothesis was analyzed using structural equation modeling. The study's findings revealed that BPM has a direct, beneficial, and statistically significant impact on corporate operations in terms of their impact on the environment (β = 0.359, P < 0.05). A good and noticeable impact on environmental performance is also produced by the indirect management of business processes through the mediation of information technology. The path coefficient and t-statistic findings indicated a positive and substantial influence of business process management on information technology. There is a clear and substantial correlation between information technology and environmental performance (β = 0.381, P < 0.05). Policy implications suggest that integrating BPM with IT solutions can significantly enhance environmental performance.